Binocular Summation and Suppression of Contrast Sensitivity in Strabismus, Fusion and Amblyopia - Dorr, Michael; Kwon, MiYoung; Lesmes, Luis Andres; Miller, Alexandra; Kazlas, Melanie; Chan, Kimberley; Hunter, David G.; Lu, Zhong-Lin; Bex, Peter J. (Frontiers in Human Neuroscience, 2019)
Purpose: Amblyopia and strabismus affect 2-5% of the population and cause a broad range of visual deficits. The response to treatment is generally assessed using visual acuity, which is relatively insensitive to binocular vision gains and may therefore underestimate binocular vision deficits in these patients. The contrast sensitivity function (CSF) generally takes longer to assess than visual acuity, but it is better correlated with improvement in a range of visual tasks and, notably, with improvements in binocular vision. The present study aims to assess monocular and binocular CSFs in amblyopia and strabismus patients. Methods: Both monocular CSFs and the binocular CSF were assessed for subjects with amblyopia (n=11), strabismus without amblyopia (n=20), and normally sighted controls (n=24) using a tablet-based implementation of the quick CSF, which can assess a full CSF in <3 minutes. Binocular summation was evaluated against a baseline model of simple probability summation. Results: The CSF of amblyopic eyes was impaired at mid-to-high spatial frequencies compared to fellow eyes, strabismic eyes without amblyopia, and control eyes. Binocular contrast summation exceeded probability summation in controls, but not in subjects with amblyopia (with or without strabismus) or strabismus without amblyopia who were able to fuse at the test distance. Binocular summation was less than probability summation in strabismic subjects who were unable to fuse. Conclusions: We conclude that monocular and binocular contrast sensitivity deficits define important characteristics of amblyopia and strabismus that are not captured by visual acuity alone and can be measured efficiently using the quick CSF.